add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
1a+3b 2a+4b=3a +7b
2a + 7b = -13a - 7b = -5The system of equations can be solved by elimination:2a + 3a = -65a = -6a = -6/5substitute the value of a in any of the two original equations to find the value of b:2(-6/5) + 7b = -1-12/5 + 1 = -7b-7/5 = -7bb= 1/5
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
Subtract 2a from each side: P - 2a = b ie b = P - 2a
3a x 2a =24
(2a + 1)(4a2 - 2a + 1)
2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
a + 7b + 2c
2(7b + 9)(b - 2)
-2a + 5 = 1 -2a = -5 + 1 -2a = -4 a = -4/-2 a = 2
a = 4
If: 2a+13 = 5a+1 Then: a = 4
2a-8+4=45-5a 2a-4=45-5a 2a-4+4=45+4-5a 2a+5a=49-5a+5a 7a=49 / by 7 = A=7
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
Firstly, I think you mean 2a-3b. The numbers always come first. Secondly, 2a-3b is an expression, not an equation as equations have equeal signs in them. Lastly, you do not have enough information to solve 2a-3b since it is an expression. Therefore, the answer to your question is 2a-3b.
Solve the following equation for A : 2A/3 = 8 + 4A
2a - 7 = -9 2a - 7 + 7 = -9 + 7 2a = -9 +7 2a = -2 2a/2 = -2/2 a = -2/2 a= -1
:a = .5(hb+c) :2a = hb+c :2a−c = hb :(2a−c)/h = b
2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------
By using the quadratic formula. (-b±√b2-4ac)/(2a)